2001
DOI: 10.1074/jbc.m003911200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Nitric Oxide Induce a Rapid, Reversible Cell Cycle Arrest of the Drosophila Syncytial Divisions

Abstract: Cells can respond to reductions in oxygen (hypoxia) by metabolic adaptations, quiescence or cell death (1). The nuclear division cycles of syncytial stage Drosophila melanogaster embryos reversibly arrest upon hypoxia. We examined this rapid arrest in real time using a fusion of green fluorescent protein and histone 2A. In addition to an interphase arrest, mitosis was specifically blocked in metaphase, much like a checkpoint arrest. Nitric oxide, recently proposed as a hypoxia signal in Drosophila, induced a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 12 publications
11
79
1
Order By: Relevance
“…3). That zebrafish embryos arrest in interphase and not mitosis contrasts with studies of Drosophila, where embryos exposed to oxygen deprivation arrest during interphase, prophase, metaphase, and telophase (11,26,27).…”
Section: Resultsmentioning
confidence: 62%
“…3). That zebrafish embryos arrest in interphase and not mitosis contrasts with studies of Drosophila, where embryos exposed to oxygen deprivation arrest during interphase, prophase, metaphase, and telophase (11,26,27).…”
Section: Resultsmentioning
confidence: 62%
“…Some of the effects of hypoxia are reversible, for example, hypoxia induces cell cycle arrest in Drosophila embryos but cell cycle activity resumes about 20 min after re-establishing normoxia (DiGregorio et al, 2001;Douglas et al, 2001). However, antibody labeling revealed that after 30 minutes of reoxygenation …”
Section: Discussionmentioning
confidence: 99%
“…NO regulates cell proliferation in the imaginal discs of developing larvae (Kuzin et al 1996) and in embryos (Wingrove and O'Farrell 1999), participates in the development of the visual system (Gibbs and Truman 1998;Gibbs 2003), induces vesicle release at the neuromuscular junction of larvae (Wildemann and Bicker 1999), controls epithelial fluid secretion by the Malpigian tubules (Dow et al 1994;Broderick et al 2003), triggers the immune response against bacterial pathogens (Nappi et al 2000), induces arrest of nuclear divisions in early embryo in response to oxygen deprivation (DiGregorio et al 2001), and mediates hypoxia-dependent exploratory behavioral responses in larvae (Wingrove and O'Farrell 1999) and hypoxia-induced stasis in embryos (Teodoro and O'Farrell 2003). This wide range of processes mediated by NO requires tight regulation of its production in response to different stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, these changes include blood-vessel relaxation, immune response, cell cycle control, and neurotransmission. In Drosophila, NO has been implicated in visual-system development, immunity, behavior, response to hypoxia, osmoregulation, and regulation of cell cycle progression during development (Dow et al 1994;Kuzin et al 1996Kuzin et al , 2000Gibbs and Truman 1998;Wingrove and O'Farrell 1999;Nappi et al 2000;DiGregorio et al 2001;Teodoro and O'Farrell 2003).…”
mentioning
confidence: 99%